Annual reviews of computational physics IX IX - Stauffer, Dietrich (Singapore World Scientific, 2001)
Computational Physics has as a special feature a comprehensive compendium of interatomic potentials as used for materials properties. Other articles deal with simulations of magnetic nanostructures, improved Monte Carlo methods
Keywords: Cơ bản